State Policy in the Field of Education during the Period of Soviet Modernization of the 1920s — 1930s (on materials of national regions of Southern Russia) - K. Lidzheeva (Oriental Studies, 2018)
The paper examines the impact of socio-economic processes to the education sector in transition to the uniﬁcation of the social life and the changes occurred as a result of the industrial express modernization on the materials on the national autonomies in the South of Russia.